Knee joint kinematic variability of the touchdown leg during the maximal velocity phase of sprint running - Gittoes, M.; Wilson, C. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study aimed to develop insight into knee joint kinematic variability of the touchdown leg during the maximal velocity phase of sprint running. Joint centre coordinate data were obtained for running trials performed by seven male athletes. Between and within athlete coefficient of variations were derived for step and sagittal plane knee joint angle variables. The minimum knee joint angle produced the largest between (13.3%) and within (8.4%) athlete variability and was related to velocity by an inverted U profile. The slowest and fastest athletes produced relatively higher step velocity variability than the intermediate athletes. The discrepancy in the within athlete step and knee joint kinematic variability of performers achieving similar gait-related objectives suggested a need to consider idiosyncratic kinematic patterns in developing sprint running performance.